The Relationship of Knowledge and Attitudes of Traders with Traditional Market Sanitation Hygiene - Fera, Dian; Nabela, Danvil; Muchsin, Sri Wahyuni; Kiswanto, Kiswanto; Iskandar, Wardah; Fahlevi, Muhammad Iqbal (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
Hygiene sanitation of the traditional market environment with conditions of ignorance of market traders must be clean from garbage, dirt in trading facilities and around the market and do not use personal protective equipment, various public health problems can occur if traders do not know and are not aware to maintain the cleanliness of market environment sanitation. The purpose of this study was to determine the relationship between knowledge and attitudes of traders with hygiene, sanitation, environment, traditional markets in Kota Fajar Village, North Kluert District, South Aceh Regency. Type of quantitative research with Cross Sectional design. The study was conducted on June 5-18, 2022 with a sample of 74 traders using a simple Random Sampling technique Data collection using questionnaires. Data analysis using univariate and bivariate analysis with chi-square test. The level of knowledge of market traders in maintaining the sanitary hygiene of the market environment was partly obtained by the results that 11 respondents 64.7% had poor knowledge with poor sanitary hygiene. Negative attitudes of 13 respondents 17.6% with poor sanitary hygiene . Based on statistical tests using chi-square, there is a relationship between the knowledge (P value 0.000) and attitude (P value 0.000) of market traders by maintaining the sanitary hygiene of the traditional market environment. It is expected that market traders will know and be aware of maintaining the cleanliness of facilities including personal protective equipment